ANALISIS PENGARUH LINGKUNGAN KERJA, KEMAMPUAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI (Studi pada Unit Pelayanan Pendapatan dan Pemberdayaan Asset Daerah Provinsi Jawa Tengah Se Koordinator Pekalongan) - Dita Putri Elfasia, 06.35.02.0737; Yunianto, Askar (Students Journal of Economic and Management, 2013)
The Reform movement that occured in Indonesia affect the livelihood in the field og governance. It is characterized by the formation of the regional Autonomy law and then updated with the law om local goverment. which in principle has been to change the system of goverment in Indonesia that will ultimately influence in the role of the civil servants of the demand a paradigm shift in completing task work as an apparatus which is concerned on duty. The research was conducted at PNS employee Revenue Service Unit and Asset Empowerment in Central Java Provincial Coordinator Pekalongan view using sensus method. All of the sample population and as many as 115 people a decent processed questionaires were 108 questionair. The result of regression testing obtained result Adjusted R square of 0.828 mean that the change of variables can be explained by the variable performance wok that the variable are jointly working environment of 82.8%. As for the F test showed that the varibles are jointly working ability and commitment affect organizational performance. based on known significant partial regression testing environment on performance is o.o18 <0.05. the significant of the ability to work on performance is 0.000 <0.05 and the significant of organizational commitment to performance is 0.000 <0.05. This indicated that all the hypothesis are accepted and proven. Key Words: work environment, worl ability, organizational commitment, performance